Robert Boyle's anonymous 'Crosey-Crucian' identified: The German alchemist and religious dissenter Peter Moritz. (20th March 2020) - Zuber, Mike A.; Penman, Leigh T. I.
Abstract : Using previously neglected manuscript sources, this paper sheds light on a puzzling episode in the later life of Robert Boyle and the early career of his laboratory assistant Ambrose Godfrey. Currently, the only account of their disappointing encounter with an unnamed German adept derives from Godfrey's lost manuscript treatise 'An Apology and Letter touching a Crosey-Crucian', excerpts of which were published in 1858. Based on a comparison between that source and the papers of the virtually forgotten chymical practitioner and convicted heretic Peter Moritz (1638– ca. 1700), the authors argue that Godfrey's anonymous 'Crosey-Crucian' was none other than Moritz himself. The first part establishes that various significant and seemingly insignificant details agree precisely and thus corroborate this identification. The second part focuses on those passages among Moritz's papers that contain explicit evidence of his dealings with both Boyle and Godfrey, a sheet of notes and a lengthy epistolary 'Memorial' to an unnamed addressee. The authors contend that Moritz's 'Memorial' is a version of the same document that the adept sought to deliver to Boyle who refused to accept it, according to Godfrey's 'Apology'. For this reason, and on the basis of strong internal evidence, Boyle is identified as the intended recipient of Moritz's 'Memorial'. Taken together, these two identifications solve a long-standing riddle in Boyle scholarship and introduce a significant addition to his extant correspondence.